MATLAB-Simulink environment based power quality improvement in photovoltaic system using multilevel inverter - Priyanka, G.; Surya Kumari, J.; Lenine, D.; Srinivasa Varma, P.; Sneha Madhuri, S.; Chandu, V. (Національний технічний університет "Харківський політехнічний інститут", 2023)
Introduction. In this world of technical advancement, conventional resources are at the stage of destruction. To avoid such problems, we are going to use an alternative energy source namely solar by photovoltaic effect. The demand for multilevel inverters increased as they are used for different dynamic (high) voltage and dynamic (high) power appliances as they are capable of producing the output wave shape with low total harmonic distortion. Novelty. A new multilevel inverter is used in adding a (bidirectional) two way switch in between the capacitor and a traditional H-bridge module. This produces a better sine wave. By series connection of these two H-bridge modules, nine levels output voltage including zero is possible. The purpose of the proposed topology is reduction in the number of switches and it gives the good result with comparatively less power loss when it is compared with the other normal basic traditional inverters of the same output quality. Methods. In this paper, sinusoidal pulse width modulation technique is used for the working of the switches in the multilevel inverter. The results are verified by using simulation and also experimental setup is done. From the results it is observed that the proposed topology with reduced number of switches gives lower electromagnetic interference, lower harmonic distortion. Practical value. The total harmonic distortion value in the simulation is 14.4 % and practically it is 13.8 %.

Вступ. У світі технічного прогресу звичайні ресурси перебувають у стадії руйнації. Щоб уникнути таких проблем, ми збираємося використати альтернативне джерело енергії, а саме сонячну енергію з фотоелектричним ефектом. Попит на багаторівневі інвертори збільшився, оскільки вони використовуються для різних динамічних (високих) напруг та динамічних (високих) потужностей, оскільки вони здатні формувати вихідну форму хвилі з низьким гармонічним загальним спотворенням. Новизна. Новий багаторівневий інвертор використовується для додавання двостороннього перемикача між конденсатором і традиційним модулем Н-моста. Це дає найкращу синусоїду. При послідовному з'єднанні двох модулів Н-моста можливо дев'ять рівнів вихідної напруги, включаючи нуль. Метою запропонованої топології є зменшення кількості перемикачів, що дає хороший результат при порівняно менших втратах потужності порівняно з іншими традиційними звичайними інверторами з такою ж вихідною якістю. Методи. У цій статті для роботи перемикачів у багаторівневому інверторі використовується метод широтно-імпульсної синусоїдальної модуляції. Результати перевіряються за допомогою моделювання, а також виконується експеримент. З результатів видно, що пропонована топологія зі зменшеною кількістю перемикачів дає менші електромагнітні перешкоди, менші гармонійні спотворення. Практична цінність. Сумарне значення гармонійних спотворень при моделюванні складає 14,4 %, а практично – 13,8 %.
Keywords: multilevel inverter; pulse width modulation; cascaded multilevel inverter; standard test conditions; cascaded H-bridge multilevel; space vector modulation; багаторівневий інвертор; широтно-імпульсна модуляція; каскадний багаторівневий інвертор; стандартні умови випробувань; каскадний багаторівневий Н-міст; просторово-векторна модуляція